Primary prevention programs for childhood obesity: are they cost-effective? - Miriana Guarino; Lorena Matonti; Francesco Chiarelli; Annalisa Blasetti (BMC, 2023)
Abstract Childhood obesity is increasing all over the world. It is associated with a reduction in quality of life and a relevant burden on society costs. This systematic review deals with the cost-effectiveness analysis (CEA) of primary prevention programs on childhood overweight/obesity, in order to benefit from cost-effective interventions. We screened and evaluated all the studies with a cost-effectiveness analysis on childhood obesity primary prevention program by PUBMED and Google Scholar, using inclusion and exclusion criteria. The quality of the studies was assessed by Drummond's checklist. Ten studies were included. Two of them examined the cost-effectiveness of community-based prevention programs, four focused only on school-based programs while four more studies examined both community-based and school-based programs. The studies were different in terms of study design, target population, health and economic outcomes. Seventy per cent of the works had positive economic results. The majority of the studies showed effective economic outcomes applying primary prevention programs on childhood obesity. It is important to increase homogeneity and consistency among different studies.